1996
DOI: 10.1002/(sici)1097-0215(19960315)65:6<805::aid-ijc17>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 (IL-1) production is not essential for acquired resistance of human A375 melanoma cells to anti-proliferative effect of IL-1

Abstract: The proliferation of human melanoma cell line A375-6 is inhibited by interleukin I (IL-I). However, the cells acquired resistance to IL-I after a long period of culture. We have reported that 2 resistant subclones, A375-R8 and -R19, produced IL-la constitutively and that IL-I induced IL-6 production in an autocrine manner. Therefore, we supposed that IL-la production renders the cells resistant to IL-I. To investigate the relationship between IL-la production and IL-I resistance, we transfected the IL-I a expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…First, secretion of IL-1β, which under normal conditions is strictly regulated, becomes constitutive in some melanoma cells [3,4]. Second, melanoma cells can acquire resistance to the direct anti-proliferative/cytotoxic effects of this cytokine [5,6].Further advancement in this area was recently reported by Okammoto and Fujita who correlated melanoma aggressiveness to constitutive IL-1β secretion [2]. Their work showed that loss of inflammasome regulation and autonomous IL-1β secretion was limited to advanced but not early-stage melanoma cells.…”
Section: Inflammasome and Il1β In Melanomamentioning
confidence: 99%
“…First, secretion of IL-1β, which under normal conditions is strictly regulated, becomes constitutive in some melanoma cells [3,4]. Second, melanoma cells can acquire resistance to the direct anti-proliferative/cytotoxic effects of this cytokine [5,6].Further advancement in this area was recently reported by Okammoto and Fujita who correlated melanoma aggressiveness to constitutive IL-1β secretion [2]. Their work showed that loss of inflammasome regulation and autonomous IL-1β secretion was limited to advanced but not early-stage melanoma cells.…”
Section: Inflammasome and Il1β In Melanomamentioning
confidence: 99%